Estimación de la huella de carbono en parcelas de quinua orgánica en el sur de Bolivia: Estudio de caso - Liliana Carolina Roca Villarroel (Institute for Advanced Development Studies (INESAD), 2024)
– This case study is part of the research project "Creating Indigenous Women's Green Jobs under Low-Carbon COVID-19 Response and Recovery in the Bolivian Quinoa Sector). I estimate the carbon footprint associated with the quinoa production in southern Bolivia based on primary information of 19 plots. Using a cradle-to-gate life cycle analysis approach, under the ISO 14067 standard, and analyzing various emission sources through the Cool Farm Tool, I determine that the carbon footprint generates an average of 741 .7 kg CO2e per plot; and an average of 267.4 kg CO2e per hectare. The main emission sources identified are the use of organic fertilizer (54%), the consumption of fossil fuels (35%) and the use of protection inputs (8%). Considering the declared unit of 1 kg of harvested quinoa, I obtain the carbon footprint results per product, with values ranging between 0.3 and 2.3 kg CO2e/kg of quinoa and an average of 0.98 kg CO2e/ kg of quinoa.
Keywords: Q16; Q29; Q54; Y8; 330; climate change; carbon footprint; quinoa crops